Information disclosure and vaccination externalities. (22nd August 2013) - Shi, Xinyan
Abstract: This paper examines the information disclosure problem when both positive and negative externalities can arise for vaccination. During an epidemic outbreak, public disclosure on the level of infectiousness may potentially trigger a sudden increase in the demand for vaccination, which imposes external costs. The government has to choose an information disclosure policy to induce a level of vaccination that balances the benefits and costs of revealing information. I establish conditions under which a full disclosure is optimal in some circumstances and a non‐disclosure or partial disclosure is optimal in other circumstances. I show that the feature of partial convexity restricts the scenarios in which pooling is desirable. Indeed, I find that it is never optimal to pool a sufficiently low infectiousness state with other states.